Community changes at the North Siberian margin in response to Atlantic water mass variability since last deglacial times - Taldenkova, Ekaterina; Bauch, Henning; Stepanova, Anna; Ovsepyan, Yaroslav; Nikolaev, Sergei (University of Oulu and Thule Institute, 2012)
The eastward penetration of Atlantic-derived water (ADW) into the Eurasian Basin of the Arctic Ocean was investigated at the western Laptev Sea continental margin for the time since c. 17.6 ka. Using a high-resolution investigation of the lithology, geochemistry, planktic and benthic foraminifers, and ostracods on a sediment core from 270 m water depth major steps in the environmental evolution of the region are recognized. In general, ADW was continuously present in the study area. Between 17.6 and 15.4 ka ADW manifested itself through open-water polynyas and associated upwelling events. Comparison between the Laptev Sea and northern Svalbard shelf using Cassidulina neoteretis allows assuming an unmodified subsurface inflow of ADW within its northern branch between 15.4-13.2, which was strongest after 14.7 ka and in line with the overall climate amelioration. A local freshwater event at 13 ka followed by shelf flooding and the establishment of a freshened shelf water mass resulted in an off-shelf displacement of ADW from the studied site as suggested by the disappearance of C. neoteretis between 12 and 7 ka. As evidenced by an abundance peak in Nonion labradoricum, the sea-ice marginal zone was located at the site around 12-11 ka but then shifted northward during the early Holocene warming. Enhanced ADW inflow since 7 ka correlated with climate cooling and southward retreat of the seasonal drift-ice margin. The inflow of ADW during mid-late Holocene differed from deglacial times because of the combined influence of northern and eastern ADW branches.